2011
DOI: 10.1039/c1jm12516h
|View full text |Cite
|
Sign up to set email alerts
|

Fabrics with self-adaptive wettability controlled by “light-and-dark”

Abstract: Self-adaptive wettability is built on fibrous textile material through a simple one-step fabric treatment with nanotitania followed by controlled exposure to ''light'' and ''dark''. The self-adaptive feature created a fabric with one side having superhydrophilic and the other having hydrophobic properties. With the two contrasting properties, water can be transported unidirectionally from the hydrophobic side to the superhydrophilic side through the cooperation of 2D nano-capillary and 3D marco-capillary chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
59
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 27 publications
1
59
0
Order By: Relevance
“…However, no water can be transferred in opposite way through the fabric unless an extra pressure was applied to assist in the penetration. A similar result was also reported by Kong et al9 who showed that directional water transport can be formed on superhydrophobic fabric through light irradiation. Apart from the formation of wettability gradient across the thickness of fabric, abruptly changed wettability between hydrophobicity and hydrophilicity in thin nanofibrous membranes also showed directional water transport effect10.…”
supporting
confidence: 89%
“…However, no water can be transferred in opposite way through the fabric unless an extra pressure was applied to assist in the penetration. A similar result was also reported by Kong et al9 who showed that directional water transport can be formed on superhydrophobic fabric through light irradiation. Apart from the formation of wettability gradient across the thickness of fabric, abruptly changed wettability between hydrophobicity and hydrophilicity in thin nanofibrous membranes also showed directional water transport effect10.…”
supporting
confidence: 89%
“…For example, Wang et al and Zhou et al from our group [11][12][13] and Kong et al [14] have separately reported the preparation of directional water transport fabrics through a two-step process involving superhydrophobic treatment of fabric followed by one-side photo-degradation to create a hydrophobicity-to-hydrophilicity gradient through fabric thickness. Zhang et al [15] used a phase separation method to form a hydrophilic-to-hydrophobic gradient membrane showing directional water transport ability.…”
Section: Doi: 101002/admi201600036mentioning
confidence: 98%
“…Directional water transport through fabrics is ascribed to isotropic wettability along the fabric thickness. [3,11,13,14,19] Directional water transport fabrics show difference in water breakthrough pressure on the two fabric sides. [11][12][13]17] However, the lack of effective technique to precisely control the coating layer thickness has confined the study on the role of hydrophobic fabric layer thickness in forming directional water transport on conventional fabrics.…”
Section: Doi: 101002/admi201600036mentioning
confidence: 99%
“…Titania nanoparticles are widely used not only in paint 7 , papermaking 8 , plastics 9 , cosmetics 10 , but also applied in many special research fields such as antibacterial 11 , anticorrosion 12 , antifogging 13 , biomedical 14 , fluid transportation 15 , liquid separation 16 , offset printing and liquid reprography 17 , self-cleaning 18 , site-selective functional patterning 19 and water condensation 20 . Physical and chemical properties of TiO 2 nanoparticles are affected not only by molecular structure, but also by their size, shape, organization, and surface properties.…”
Section: Introductionmentioning
confidence: 99%